A bill to pay tales jurors (House doc. (North Carolina. General Assembly. House of Commons), 1852)
1852 North Carolina House bill and its proposed substitute to pay Tales Jurors who are summoned to serve in various courts the same per diem compensation and mileage as jurors who were summoned on the original panel. Of note, a tales juror was summoned from the surrounding area, generally when summoned jurors failed to show up in sufficient numbers.